Strength, Stamina, and Sexism in the 2016 Presidential Race. Issue 1 (10th April 2018) - Conroy, Meredith
Abstract : On September 11, 2016, less than two months before Election Day, Hillary Clinton attended the 9/11 memorial service in New York City. Reportedly, Clinton left the event early, and as she was getting into her SUV, she fainted. A bystander caught on camera a wobbly Clinton needing assistance getting into her vehicle, which he posted to Twitter, where it immediately circulated (Kafka 2016). News media outlets soon picked it up and were quick to air the footage. Initially, the Clinton campaign explained that Clinton had been "overheated." Later that afternoon, however, the campaign announced that two days prior, Clinton had been diagnosed with walking pneumonia, and despite being advised to rest, she had attended the memorial event.